Film Sebagai Medium Komunikasi Pariwisata (Storynomics Tourism dalam Film “Ngeri-Ngeri Sedap”) - Mazaya, Zahra; Susilawati, Novi; Nisa, Uswatun (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
Ngeri-Ngeri Sedap is a film set in the Batak tribe that has successfully introduced North Sumatra tourism to a culture that attracts the attention of the audience. This research aims to see how Ngeri-Ngeri Sedap movie can be a medium of communication in the field of tourism through the tourism storynomics approach. The theory used in this research is McLuhan's Media Ecology Theory. This research uses a qualitative approach with descriptive methods, and data collection techniques through interviews, observation, and documentation. The results of this study show that the elements of narrative, living culture, and culture in the Ngeri-Ngeri Sedap film have succeeded in becoming a tourism communication medium that can effectively reach and mobilize the public to visit tourist destinations and also be proud to preserve Batak culture as depicted in the film. Researchers also found factors such as cultural understanding, profession, and hobbies that influence the elements of narrative, living culture, and culture. Holbung Hill Tourism and Tarabunga Village managed to get an increase in visitors and had a significant impact on improving the economy of the local Bumdes. After the visit, visitors implement tourism storynomics on social media which has an impact on visitor participation in promoting tourist destinations again.